Potential viral pathogenic mechanism in human type 1 diabetes - Schneider, Darius A.; von Herrath, Matthias G. (Diabetologia, 2014)
In type 1 diabetes, as a result of as yet unknown triggering events, auto-aggressive CD8 + T cells, together with a significant number of other inflammatory cells, including CD8 + T lymphocytes with unknown specificity, infiltrate the pancreas, leading to insulitis and destruction of the insulin-producing beta cells. Type 1 diabetes is a multifactorial disease caused by an interactive combination of genetic and environmental factors. Viruses are major environmental candidates with known potential effects on specific key points in the pathogenesis of type 1 diabetes and recent findings seem to confirm this presumption. However, we still lack well-grounded mechanistic explanations for how exactly viruses may influence type 1 diabetes aetiology. In this review we provide a summary of experimentally defined viral mechanisms potentially involved in the ontology of type 1 diabetes and discuss some novel hypotheses of how viruses may affect the initiation and natural history of the disease.